Fiscal Risks : Sources, Disclosure, and Management. (Policy Papers; Policy Paper ;, 2008)
A number of member countries have expressed interest in advice regarding disclosure and management of fiscal risks (defined as the possibility of deviations of fiscal outcomes from what was expected at the time of the budget or other forecast). This paper analyzes the main sources of fiscal risks and-building on an overview of existing practices in a wide range of countries-provides practical suggestions in this area, including a possible Statement of Fiscal Risks and a set of Guidelines for Fiscal Risk Disclosure and Management.